2017
DOI: 10.1111/aor.12861
|View full text |Cite
|
Sign up to set email alerts
|

Routine Use of Distal Arterial Perfusion in Pediatric Femoral Venoarterial Extracorporeal Membrane Oxygenation

Abstract: Lower-extremity ischemia is a significant complication in children on femoral venoarterial extracorporeal membrane oxygenation (VA ECMO). Our institution currently routinely uses distal perfusion catheters (DPCs) in all femoral arterial cannulations in attempts to reduce ischemia. We performed a single-center, retrospective review of pediatric patients supported with femoral VA ECMO from January 2005 to November 2015. The outcomes of patients with prophylactic DPC placement at cannulation (prophylactic DPC) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…These results should be interpreted with caution as data on vessel patency following decannulation was not available from the registry. Early experiences with techniques for managing distal limb ischemia, such as the insertion of distal perfusion catheters with PERC or OPEN access in pediatrics, demonstrate feasibility but have not demonstrated definitive improvement in clinical outcomes (25, 26). More granular data, as may be obtained through multicenter retrospective reviews outside of registry data, is needed for detailed analyses of the use of distal perfusion techniques and more importantly, for evaluation of vessel patency and usability following decannulation (27, 28).…”
Section: Discussionmentioning
confidence: 99%
“…These results should be interpreted with caution as data on vessel patency following decannulation was not available from the registry. Early experiences with techniques for managing distal limb ischemia, such as the insertion of distal perfusion catheters with PERC or OPEN access in pediatrics, demonstrate feasibility but have not demonstrated definitive improvement in clinical outcomes (25, 26). More granular data, as may be obtained through multicenter retrospective reviews outside of registry data, is needed for detailed analyses of the use of distal perfusion techniques and more importantly, for evaluation of vessel patency and usability following decannulation (27, 28).…”
Section: Discussionmentioning
confidence: 99%
“…One approach is to insert a distal perfusion catheter into the superficial femoral artery just distal to the cannulation site for anterograde flow [ 88 90 ] or into the posterior tibial artery for retrograde flow [ 91 ]. Data are limited and inconclusive on the relative benefit of prophylactic versus reactive placement of a distal arterial perfusion catheter in the pediatric population [ 92 ]. A distal venous drainage catheter has also been described as a method to decrease tissue edema and further improve perfusion during long-term ECLS [ 88 ].…”
Section: Evolving Cannulation Strategiesmentioning
confidence: 99%
“…A distal venous drainage catheter has also been described as a method to decrease tissue edema and further improve perfusion during long-term ECLS [ 88 ]. Close monitoring of limb perfusion in any patient with femoral cannulation is critical, regardless of the presence of a distal perfusion catheter, as limb ischemia can occur even after catheter placement [ 92 , 93 ]. Alternatively, rather than inserting a distal catheter, a prosthetic graft can be sewn to the femoral artery and subsequently cannulated (“stovepipe” or “side-arm” cannulation) to prevent occlusion of the native vessel with the cannula [ 94 ].…”
Section: Evolving Cannulation Strategiesmentioning
confidence: 99%
“…Schad et al of the Columbia University Medical Center, New York, NY, USA reported on a single‐center, retrospective review of 29 pediatric patients supported with femoral venoarterial extracorporeal membrane oxygenation (VA ECMO) comparing the outcomes of patients with prophylactic distal perfusion catheter (DPC) placement at cannulation (prophylactic DPC) to a historical group with DPCs placed in response only to clinically evident ischemic changes (reactive DPC). Ischemic complications requiring invasive intervention developed in 2 of 17 prophylactic DPC patients vs. 4 of 14 reactive DPC.…”
Section: Cardiopulmonary Support and Membrane Oxygenationmentioning
confidence: 99%